PENGARUH KELOMPOK SOSIAL DAN GAYA HIDUP TERHADAP KEPTUSAN PEMBELIAN JASA GO – JEK (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAB BISNIS UNIVERSITAS ISLAM MALANG) - Mohammad Mohammad; M Hufron (UNIVERSITAS ISLAM MALANG, 2019)
Abstract The objective of this research is to influence of lifestyle and Social groups on purchasing decisions services Go – Jek at Universty of Islam Malang. This research is quantitative aiming for partial significant influence and simultaneously. The respondents number who used a total of 100 respondents who are all students of Unisma Malang. This research method is tested with validity and reliability test. The classical assumption used normality assumption test, multicollinearity assumption test, heteroscedasticity assumption test, and linearity assumption test. It is also used multiple linear regression, and test the hypothesis that F test, t test, and test the dominant. The results showed significant effect simultaneously between lifestyle variables and Social group on purchasing decisions. Keywords : Social groups, Lifestyle, on purchasing decisions